The accuracy of references in PhD theses: a case study. (22nd April 2013) - Azadeh, Fereydoon; Vaez, Reyhaneh
Abstract: Background: Inaccurate references and citations cause confusion, distrust in the accuracy of a report, waste of time and unnecessary financial charges for libraries, information centres and researchers. Objectives: The aim of the study was to establish the accuracy of article references in PhD theses from the Tehran and Tabriz Universities of Medical Sciences and their compliance with the Vancouver style. Methods: We analysed 357 article references in the Tehran and 347 in the Tabriz. Six bibliographic elements were assessed: authors' names, article title, journal title, publication year, volume and page range. Referencing errors were divided into major and minor. Results: Sixty two percent of references in the Tehran and 53% of those in the Tabriz were erroneous. In total, 164 references in the Tehran and 136 in the Tabriz were complete without error. Of 357 reference articles in the Tehran, 34 (9.8%) were in complete accordance with the Vancouver style, compared with none in the Tabriz. Accuracy of referencing did not differ significantly between the two groups, but compliance with the Vancouver style was significantly better in the Tehran. Conclusions: The accuracy of referencing was not satisfactory in both groups, and students need to gain adequate instruction in appropriate referencing methods.